STATIC CHARACTERISTICS ANALYSIS OF A RUBBER BUSHING WITH FEM SIMULATION AND EXPERIMENT - PAN Yu; HE YunFeng; HE ZhiBing (Jixie qiangdu, 2015)
In order to study the static characteristics of rubber bushings during product developing,a FEM analysis is given to one rear control arm bushing with Mooney-Rivlin constitutive model in this paper. The loads（ compression displacement,Yaw angle,torsion angle） are obtained according to the motion of the bushing under limiting case. Then,we get the axial stiffness,radial stiffness,torsion stiffness and Yaw stiffness through the software ABAQUS. Comparing the computed results with the experiment data,we find that the computing method is reliable,and can provide theoretical guidance for future busing design.